KESULITAN ORANGTUA MUALAF DALAM MEMBERIKAN PENDIDIKAN AGAMA ISLAM KEPADA ANAK REMAJANYA DI YOGYAKARTA - Waenoful Waenoful (Islamic University of Indonesia, 2018)
This study aimed to know the level of difficulty of Mualaf parents in giving islamic education to their children, especially their teenagers. The research method used is descriptive qualitative research design. Analysis of the data obtained in this study uses the Content Analysis strategy as a method of analyzing text and language. The result shows that the provision of islamic education toward teenagers is related to the teaching of monotheism, mahdoh worship and ghoiru mahdoh. Difficulties experienced include the lack of Islamic knowledge of parents and the activities of teenagers outside the home make the intensity of parents giving advice to their children less than optimal, teenagers have unstable psychological conditions that make they postpone parents’ orders, especially when ordered to perform shalat. Whereas the provision of islamic education to teenagers does not have a negative impact on children’s religious behavior, because bringing a private tutor and sending their children to Islamic school are the best solution for Mualaf parents. Keywords: Difficulties, Islamic Education, Mualaf